Technology of plasticity : selected, peer reviewed papers from the First Asia Pacific Symposium on Technology of Plasticity (APSTP 2017), November 22-25, 2017, Taichung, Taiwan - Wang, Gou-Jen; Hwang, Yeong-Maw; Fann, Kuang-Jau; Jiang, Cho-Pei (Trans Tech Publications Ltd, 2018)
This special volume includes the papers presented at the First Asia Pacific Symposium on Technology of Plasticity (APSTP 2017, National Chung Hsing University, Taichung, Taiwan, November 22-25, 2017) and covers the results of research and development in the area of the metal plasticity, metal forming processes and related technologies. Metal, Alloys, Plasticity, Formability, Metal Forming Processes and Technologies, Surface Hardness, Surface Quality, Metal Sheet, Tube Forming, Mechanical Properties, Testing, Measurement, Numerical Modeling Materials Science.